Picture Word Card Media in Early Grade Reading Achievement: Kartu Kata Gambar sebagai Media dalam Pencapaian Membaca pada Tingkat Awal - Risa Wati; Mahardika Darmawan Kusuma Wardana (Academia Open, 2025)
General Background: Early reading skills constitute a fundamental component of language development in elementary education. Specific Background: Many first-grade students still experience difficulties in recognizing letters, forming syllables, and reading simple words fluently in Indonesian language classes. Knowledge Gap: Although various visual learning media have been introduced, the structured use of picture word card media in supporting beginning reading skills requires further empirical description at the elementary level. Aims: This study aims to examine the implementation of picture word card media and to analyze its role in improving first-grade students’ beginning reading skills. Results: Using a quantitative approach with reading tests as the primary instrument, the findings indicate measurable improvement in students’ abilities to recognize letters, read syllables, and construct simple words after the application of picture word cards in classroom learning. The visual association between images and words facilitates students’ comprehension and participation during learning activities. Novelty: The study provides contextual empirical evidence on the application of picture word card media in first-grade Indonesian language instruction. Implications: The findings offer practical guidance for elementary teachers in designing visually supported literacy instruction to strengthen foundational reading competence. Keywords: Picture Word Cards, Beginning Reading, Early Literacy, Indonesian Language Learning, Elementary School Key Findings Highlights: Visual-word association supports letter and syllable recognition in first-grade learners. Structured classroom implementation increases student participation during literacy activities. Measurable score progression appears after systematic media application.